Janice VanCleave's engineering for every kid : easy activities that make learning science fun - VanCleave, Janice Pratt (VanCleave, Janice Pratt. Janice VanCleave science for every kid series., 2007)
Explains some of the basic physical principles of engineering, accompanied by activities that illustrate those principles.